2019
DOI: 10.4314/jasem.v23i9.2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vermicast on Early Growth of Black Afara (<i>Terminaliaivorensis</i> A. Chev.) Seedlings

Abstract: This study assessed the effect of vermicast on the early growth of Terminalia ivorensis A.Chev. (Black Afara) seedlings which belongs to the family Combretaceae. Seedlings were raised on Vermicast (100%), Vermicast + Topsoil (1:1,) and topsoil media. There were three (3) treatments, replicated four (4) times and laid in Completely Randomized Design (CRD). The experiment was monitored for 12 weeks and the following variables were assessed, plant height (cm), stem diameter (mm), leaf production and the leaf area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Zaman (2015) [31] reported that the application of vermicompost increased the plant height, number of branches and dry weight of leaves in Stevia with the advancement of growth period (60 DAP). Aderourmu and Gunwande (2019) [1] also reported similar results in black afara (Terminalia ivorensis). Oyedegi et al (2014) [20] observed that, with the NPK treatment having the significantly highest number of branches, fresh and dry weight than organic manures in Amaranthus deflexus and three species.…”
Section: Discussionmentioning
confidence: 53%
“…Zaman (2015) [31] reported that the application of vermicompost increased the plant height, number of branches and dry weight of leaves in Stevia with the advancement of growth period (60 DAP). Aderourmu and Gunwande (2019) [1] also reported similar results in black afara (Terminalia ivorensis). Oyedegi et al (2014) [20] observed that, with the NPK treatment having the significantly highest number of branches, fresh and dry weight than organic manures in Amaranthus deflexus and three species.…”
Section: Discussionmentioning
confidence: 53%